Studi pengalokasian ruang terbuka hijau berdasarkan kenyamanan termal di Desa Dauh Puri Kaja, Denpasar Utara, Bali - Dhiva Laksmitha Puspa Indra Dewata; I Gusti Agung Ayu Rai Asmiwyati (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Dauh Puri Kaja Village, located in the North Denpasar District of Bali, is the village with the highest population density in the district. This has resulted in Dauh Puri Kaja Village being dominated by built-up areas, consisting mostly of residential settlements with moderate to high building base coefficients, as well as commercial areas such as shophouses and office buildings. This research aimed to determine the influence of land cover types on the level of thermal comfort in Dauh Puri Kaja Village based on the Temperature Humidity Index (THI). The method used in this research was a survey method with quantitative descriptive data. The research stages included preparation, inventory, analysis, synthesis, and recommendations. The results showed that thermal conditions in DauhPuri Kaja Village were generally uncomfortable, with an average daily THI of 29.7. The existing land cover in the village consisted of 70% paved surfaces, 25% green open space, and 5% water bodies. Therefore, to achieve ideal thermal comfort with a target THI value of 26, this study recommends increasing green open space by 21.54 hectares, or 20% of the total area of Dauh Puri Kaja Village. This recommendation was based on the results of a linear regression analysis, which identified a correlation between thermal comfort levels and land cover. The addition of green open space could be realized through the development of community parks and the regulation of yard usage.